The Impact of Anti-rheumatic Drugs on the Seroprevalence of Anti-SARS-CoV-2 Antibodies in a Cohort of Patients With Inflammatory Arthritis: The MAINSTREAM Study - Ennio Giulio Favalli; Ennio Giulio Favalli; Andrea Gobbini; Mauro Bombaci; Gabriella Maioli; Gabriella Maioli; Martina Biggioggero; Elisa Pesce; Andrea Favalli; Martina Martinovic; Tanya Fabbris; Edoardo Marchisio; et al. (Frontiers in Medicine, 2022)
ObjectivesGiven the high occurrence of asymptomatic subsets, the true prevalence of SARS-CoV-2 infection in rheumatic patients is still underestimated. This study aims to evaluate the seroprevalence of SARS-CoV-2 antibodies in rheumatic musculoskeletal diseases (RMD) patients receiving immunomodulatory drugs.MethodsAll consecutive patients with rheumatoid arthritis or spondyloarthritis receiving disease-modifying antirheumatic drugs (DMARDs) evaluated between 4th May and 16th June 2020 were included. All participants were tested for anti-SARS-CoV-2 antibodies (IgG, IgM, IgA) by ELISA and were questioned about previous COVID-19 symptoms and clinical course. Results were compared with healthy population from the same region and with a control group of healthy subjects diagnosed with confirmed COVID-19.ResultsThe study population includes 358 patients. The overall prevalence of anti-SARS-CoV-2 antibodies (18.4%) was higher than prevalence rate based on swab-positivity (1.12%) or clinically suspected cases (10.6%), but consistent with seroprevalence observed in the healthy population. Among seropositive patients 58% were asymptomatic. Mean anti-SARS-CoV-2 titer was comparable with the control group. No differences in seroprevalence were observed according to age, sex, rheumatic disease and treatment with conventional, biologic or targeted synthetic DMARDs, whereas glucocorticoids and comorbidities resulted in higher seroprevalence rate.ConclusionsThe results of this study are reassuring about the low impact of RMDs and immunomodulatory therapies on the risk and clinical course of COVID-19 and on humoral immune response to SARS-CoV-2 infection.